Strategi Pemberdayaan Petani Jagung Akibat Perubahan Iklim di Kecamatan Cijeungjing Kabupaten Ciamis - Ivan Sayid Nurahman; Iwan Setiawan; Eka Purna Yudha; Muhamad Nurdin Yusuf (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Climate change causes rainfall in most parts of Indonesia to decrease. Climate change means farmers are no longer able to use local knowledge to predict climate, thereby reducing the level of corn commodity productivity. Cijeungjing District is one of the corn production centers in Ciamis Regency, which is affected by climate change due to rain-fed agriculture. This research aims to determine the adaptation strategies of corn farmers in response to climate change, and to analyze appropriate strategies for empowering these farmers. This research uses a qualitative research method with a descriptive approach carried out through observation, interviews, and documentation. The research subjects included corn farmers who were recruited through snowball sampling. The Miles and Huberman data analysis model is used for data analysis. The results show that local farmers have implemented adaptation strategies for corn farmers due to climate change, namely: 25 percent of farmers changed planting times, 10 percent of farmers changed crop varieties, and 65 percent of farmers left their land fallow. Relevant empowerment strategies include: introduction of corn varieties that are resistant to extreme climatic conditions; development of efficient irrigation systems and soil conservation to overcome the problems of drought and soil erosion due to climate change; training and counseling for farmers to implement agricultural practices that are environmentally friendly and adaptive to climate change; and institutional support that facilitates corn farmers' access to the information, resources, and technology needed to deal with climate change.